2010
DOI: 10.1016/j.sbspro.2010.03.872
|View full text |Cite
|
Sign up to set email alerts
|

Towards a learning city the neighborhood lab and the lab net

Abstract: A local administration can develop learning policies aiming at improving the economical and productive capacities and regenerating the urban contexts: the city physical and social requalification can indeed be carried out even by building up a learning community as a crucial development tool. The district labs and networks - socio-technical places aiming at properly requalifying/maintaining/using cities - can build, in such a scenery, a strong means of physical requalification and evolution of the social capit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Alternatives to teaching and learning environments use the common laboratory methodological strategies, but a social innovation lab experiments with responding to the local and social problems of a context through networking. The most common model is through the development of participation and discussion workshops, taking into account the point of view of the communities [19].…”
Section: What Are the Concepts Related To Social Innovation Laboratories?mentioning
confidence: 99%
“…Alternatives to teaching and learning environments use the common laboratory methodological strategies, but a social innovation lab experiments with responding to the local and social problems of a context through networking. The most common model is through the development of participation and discussion workshops, taking into account the point of view of the communities [19].…”
Section: What Are the Concepts Related To Social Innovation Laboratories?mentioning
confidence: 99%
“…Hamilton (2010) concluded in a study entitled Learning City that learning cities in the UK should increase investment, create a network of learning cities, collaborate and collaborate among different organizations, education, business, local government, private sector, etc. To be In a study titled "Learning cities", Di Sivoa and Ladianaa (2010) concluded that learning society is a social one in which learning is extensive and lifelong. Activating the lifelong learning process as a fundamental strategy is to create conditions for improvement from the social, economic, political, and cultural perspective, as well as to improve the quality of life of citizens.…”
Section: Introductionmentioning
confidence: 99%